Multicultural Education in Indonesia: A Comparison with Educational Practices in Multinational Countries - Judijanto, Loso; Atikah, Nur; Akbar, Riolandi; Sapulete, Jance J; Fauzi, Muhammad Sukron; Naofal, Muhammad (The Future of Education Journal, 2025)
Multicultural education is a crucial approach to addressing the increasing complexity of cultural, ethnic, and religious diversity, particularly in Indonesia as a multicultural nation. This study aims to analyze the implementation of multicultural education in Indonesia and to compare it with practices in multinational countries such as Canada and Australia. The research employed a literature review method by analyzing various scholarly sources, including journal articles, books, research reports, and relevant national and international education policies published between 2015 and 2025. The findings indicate that although Indonesia has established policy frameworks supporting multicultural education, its implementation continues to face significant challenges, particularly in integrating multicultural values into the curriculum and in the limited availability of teacher training for managing cultural diversity in the classroom. In contrast, Canada and Australia demonstrate more systematic and integrated practices of multicultural education, despite ongoing challenges related to socio-economic disparities. The study concludes that the gap between policy and practice remains the primary barrier to the effective implementation of multicultural education in Indonesia. Therefore, a more holistic policy reformulation, the development of inclusive curricula, and the strengthening of teacher competencies are necessary to ensure that multicultural education can be implemented effectively and sustainably.